Human chorionic gonadotropin (hCG) up-regulates wnt5b and wnt7b in the mammary gland, and hCGbeta transgenic female mice present with mammary Gland tumors exhibiting characteristics of the Wnt/beta-catenin pathway activation - Kuorelahti, Aino (2007)
Transgenic (TG) mice expressing human chorionic gonadotropin (hCG) beta-subunit under the ubiquitin C promoter, presenting with a moderately elevated level of LH/hCG bioactivity develop multiple neoplasms secondary to the endocrine abnormalities, including mammary gland tumors after the age of 9 months. The increased levels of circulating estradiol, progesterone, and prolactin of the TG females after puberty boost the lobuloalveolar development in the mammary gland resulting ultimately in the formation of estrogen and progesterone receptor-negative, malignant tumors. These tumors have a similar histopathology with those observed in TG mice with activated wnt/beta-catenin pathway, showing increased expression of beta-catenin, also a common finding in human breast tumors. Transdifferentiation is observed in mammary tumors of the hCGbeta TG mice, accompanied by abnormal expression of the Wnt genes in the tumorous and nontumorous mammary gland tissue. Specifically we found increased expression of Wnt5b in the TG mammary glands at the age of 3 months and up-regulation of Wnt7b and -5b in the subsequently appearing tumors. Importantly, hCG was found to up-regulate these wnt ligands in mouse mammary gland, independent of the changes in ovarian steroidogenesis. Thus, the hCGbeta-overexpressing TG mice represent a novel model that links enhanced hCG action to dysregulated wnt signaling in the mammary gland, resulting in beta-catenin-stabilizing mammary tumorigenesis. The novel finding of hCG up-regulating wnt7b and wnt5b could contribute to pregnancy-induced breast cancer in humans.